(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article provides a detailed analysis of the economic and material life of the Surkhandarya region during the Second World War, cotton cultivation, agricultural production, industrial development and assistance to the front. Products and resources sent to the front by the residents of Surkhandarya, as well as changes in the economic recovery of the region, are considered on the basis of statistical data. The article provides information on the cultivation of cotton, increase of agricultural products, the development of industrial branches and the participants of the fighters who went to the front.